U-spin conjugate CP violation relations in bottom baryon decays - Bo-Nan Zhang; Di Wang (Physics Letters B, 2025)
Motivated by the first observation of CP violation in baryon decays, we study the relations for CP asymmetries of bottom baryon decays. It is found that all the CP violation ratios of two U-spin conjugate decay channels satisfy a simple equation in the U-spin limit. As examples, we present the U-spin conjugate channels in the four-body decays of bottom baryons. The CP violation ratios between them might provide predictions for unobserved channels and be tested in future experiments.